Restricting the use of cars by license plate numbers: a misguided urban transport policy (2014)
Several conurbations in Latin America have implemented policies to restrict the use of private cars by prohibiting those with a license plate number ending on some digit, which vary each day, from circulating on that weekday. These policies have been formulated as a “second best” option to congestion charging as the latter policy has been deemed politically unfeasible so far. The idea underlying license plate restrictions is very simple: by not allowing a proportion of the total number of vehicles to circulate on a given day, congestion levels and other externalities are expected to decrease, improving the quality of life for people. Based on a simple microeconomic analysis, supported by a review of the literature and by evidence collected in several cities where these restrictions have been implemented, it is concluded that the policy is apparently effective only in the very short-term, but ultimately it fails to achieve its objectives and usually leads to a worse outcome.